Preventing Hydrogen Disposal Increases Electrode Utilization Efficiency by Shewanella oneidensis - Joshi, Komal; Kane, Aunica L.; Kotloski, Nicholas J.; Gralnick, Jeffrey A.; Bond, Daniel R. (Frontiers in Energy Research, 2019)
Many bacteria use hydrogen anaerobically as both a source and sink for electrons; consuming hydrogen when it is plentiful and producing it when concentrations are low enough to allow proton reduction. While this can increase an organism's competitiveness, hydrogen uptake, or excretion can also make it difficult to control electron flux to a specific product. For example, when Shewanella oneidensis strain MR-1 is used to oxidize organic molecules and recover electrons in microbial electrochemical devices, small changes in ambient hydrogen concentrations could dramatically alter the efficiency of electron capture at the anode due to this organism's respiratory flexibility. When new three-electrode reactor designs created to minimize oxygen intrusion during anodic growth were tested with lactate-oxidizing S. oneidensis, current production decreased significantly in reactors vented to remove hydrogen produced at the counter electrode, suggesting a role for hydrogen uptake or disposal when cells used electrodes as electron acceptors. A ΔhydAΔhyaB mutant lacking both hydrogenases reversed this trend, and nearly doubled current production rates. This increase was shown to be due to the efficiency of lactate oxidation, as 90% of electrons were recovered as electricity in the ΔhydAΔhyaB mutant compared to only 50% for wild type. Experiments with Fe(III) oxide provided additional evidence that S. oneidensis generates hydrogen reducing equivalents during reduction of insoluble electron acceptors, while experiments with cells incubated with Fe(III) citrate showed increased survival of wild-type compared to ΔhydAΔhyaB in stationary phase. Together these data show how the multiple routes of electron disposal of S. oneidensis, while beneficial under changing conditions, limits the efficiency of electron recovery in electrochemical systems, and demonstrates a simple approach to increasing current production rates in systems where hydrogen is being captured as a product.